The Transformational Leadership and School Culture on The Learning Organization Capacity in Vocational Schools - Masbirorotni Masbirorotni; Robin Pratama; Nunung Fajaryani; Mukhlash Abrar (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2022)
This study aimed to examine the direct and indirect effects of principals' transformational leadership with school culture as a moderator variable on the capacity of learning organizations. By proposing and testing a conceptual model, this study examined the two main variables as determinants of Learning Organization (LO) capacity with the target respondents were teachers in State Vocational High Schools in Jambi City. This study used a quantitative approach with a cross sectional survey design. A total of 599 state vocational high school teachers in Jambi City were involved in this research survey. Of 599 teachers, there were only 365 data acceptable to be analyzed. Partial Least Square – Structural Equational Model (PLS-SEM) was used at the stage of model measurement and hypothesis testing. The study indicated that leadership implementation and school culture that had been applied to increase organizational learning is in progress.